Overhangs at Town Hall - Ghosh, Ayan (2023)
The Town Hall has extended overhangs that cover the doors and windows. They are protected from rain during the monsoon season. The overhangs are made of decorative wooden panels and supported on brackets. The window blinds are made from horizontal wooden slats (Venetian blinds), giving protection from the scorching sun during summer.